Parents Knowledge About First Aid For Febrile Seizures In Children At Santa Elisabeth Hospital Medan 2024 - Yein Concita Lingga; Helinida Saragih; Friska Sembiring; Samfriati Sinurat (Universitas Muhammadiyah Manado, 2024)
Parents knowledge about first aid for febrile convulsions in children can be seen from the actions taken by parents when their children have febrile convulsions. The first aid action taken by parents is an understanding of the help of febrile seizures in children. Extracranial processes and too rapid an increase in body temperature cause febrile seizures. If a person's body temperature rises and is not controlled quickly, this can lead to febrile seizures. Febrile convulsions are rapid, transient, or sudden changes in brain function with a rise in body temperature > 38°C. This study aims to describe parents' knowledge about first aid for febrile seizures. The method uses is descriptive method with the number of samples of this study 67 respondents. Data collection techniques are carried out by distributing questionnaires. The results of this study show that parental knowledge in the good knowledge category are 24 respondents (37.70%), sufficient knowledge are 33 respondents (47.54%) and poor knowledge are 10 respondents (14.75%). This study conclud that the knowledge of parents about first aid for febrile seizures in children was in the moderate category. Parents state that parents always measure their children's body temperature using a thermometer when they have a fever and always accompany their children when they have febrile seizures. The results of this study are expected to provide information to health workers and provide information to parents regarding first aid for febrile seizures in children to help and teach parents to perform good and correct febrile seizures.